2018
DOI: 10.1016/j.molp.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Allotetraploid Tobacco Genome due to Frequent Homeologous Recombination, Segmental Deletion, and Chromosome Loss

Abstract: The types of mutations and their corresponding frequencies are difficult to measure in complex genomes. In this study, a high-throughput method was developed to identify spontaneous loss-of-function alleles for the resistance gene N and the transgenic avirulence gene P50 in allotetraploid tobacco. A total of 2134 loss-of-function alleles of the N gene were identified after screening 14 million F hybrids. Analysis of these mutants revealed striking evolutionary patterns for genes in polyploids. Only 14 of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Homoeologous exchanges are now known to be common in synthetic polyploids, as well as those of recent evolutionary origin. Recent allopolyploids with commonly detected HEs include Tragopogon species ( Chester et al, 2012 ), peanuts ( Arachis hypogaea ; Bertioli et al, 2019 ; Zhuang et al, 2019 ), quinoa ( Chenopodium quinoa ; Jarvis et al, 2017 ), tobacco ( Nicotiana tabacum ; Chen et al, 2018 ) and rapeseed ( Brassica napus ; Chalhoub et al, 2014 ). Synthetics with frequent HEs include allopolyploid rice (constructed from Oryza sativa subsp.…”
Section: Homoeologous Exchanges In Allopolyploidsmentioning
confidence: 99%
“…Homoeologous exchanges are now known to be common in synthetic polyploids, as well as those of recent evolutionary origin. Recent allopolyploids with commonly detected HEs include Tragopogon species ( Chester et al, 2012 ), peanuts ( Arachis hypogaea ; Bertioli et al, 2019 ; Zhuang et al, 2019 ), quinoa ( Chenopodium quinoa ; Jarvis et al, 2017 ), tobacco ( Nicotiana tabacum ; Chen et al, 2018 ) and rapeseed ( Brassica napus ; Chalhoub et al, 2014 ). Synthetics with frequent HEs include allopolyploid rice (constructed from Oryza sativa subsp.…”
Section: Homoeologous Exchanges In Allopolyploidsmentioning
confidence: 99%
“…Classically recognized as homoeologous translocations or transpositions, the genomics era and the successful sequencing of polyploid plants ushered in an increasing realization that HEs represent a fundamental mechanism of allopolyploid genome evolution and for generating diversity. Recent illustrative examples include peanuts ( Arachis hypogaea ; Bertioli et al, 2019 ; Zhuang et al, 2019 ), Tragopogon ( Chester et al, 2012 ), quinoa ( Chenopodium quinoa ; Jarvis et al, 2017 ), Brassica ( Hurgobin et al, 2018 ; Samans et al, 2018 ), tobacco ( Nicotiana tabacum ; Chen et al, 2018 ) and allopolyploid rice (constructed from Oryza sativa subsp. indica × subsp.…”
Section: Responses To Genome Merger At the Genetic And Genomic Levelmentioning
confidence: 99%
“…Repeated allopolyploid formation or gene flow from diploids (e.g., Brachypodium hybridum - [122], Arabidopsis suecica - [174]) can cause N e to differ across subgenomes. Finally, recombination could also act to bias inferences of ω artifactually because genetic material exchanged across subgenomes via homoeologous exchange [18][19][20][21][22][23][24][25][175][176][177][178][179][180][181][182][183], gene conversion [19,20,57,62,133,153,[184][185][186][187][188][189], and other recombinational mechanisms (e.g., [190]) would be expected to bias ω inferred across a topologically constrained tree. However, we took steps to prevent this type of artifact from influencing our data by only including genes that exhibited gene-tree topologies that were consistent with the species tree topology.…”
Section: Differential Rates Of Protein-sequence Evolution Across Allopolyploid Subgenomesmentioning
confidence: 99%
“…Accordingly, evolutionary biologists have had a great deal of interest in exploring the consequences of and responses to WGD. The ensuing studies have shown that the effects of WGDs are far-ranging, including silencing and loss of duplicated genes [5][6][7][8][9][10][11], mobilization of previously dormant transposable elements [12][13][14][15][16][17], inter-genomic gene conversion and homoeologous chromosome exchanges [18][19][20][21][22][23][24][25], alterations of epigenetic marks [26][27][28][29][30][31][32][33], massive, genome-wide transcriptional rewiring [6,[34][35][36][37][38][39][40][41], and a host of other associated physiological, ecological, and life-history changes [42][43][44][45][46][47][48][49]…”
Section: Introductionmentioning
confidence: 99%